2012
DOI: 10.4141/cjss2010-056
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of an organic residual cover on tailings for bioenergy crop production: A preliminary assessment

Abstract: Hargreaves, J., Lock, A., Beckett, P., Spiers, G. A., Tisch, B, Lanteigne, L., Posadowski, T. and Soenens, M. 2012. Suitability of an organic residual cover on tailings for bioenergy crop production: A preliminary assessment. Can. J. Soil Sci. 92: 203–211. To test the potential for production of bioenergy crops, such as canola and corn, an organic cover was constructed over acid-producing mine tailings containing nickel and copper, belonging to Vale in Sudbury, Ontario, Canada. The 1 m deep cover was of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Adding any capping soil regardless of depth reduced foliar concentrations of Al, Cr, and Ti. Hargreaves et al (2012) had similar findings in a study that added a cap of organic residuals over mine tailings containing nickel and copper and showed no evidence of metal movement over the course of the 2 yr study. Evaluating trace metal accumulation in the roots of willows should be further investigated in future studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Adding any capping soil regardless of depth reduced foliar concentrations of Al, Cr, and Ti. Hargreaves et al (2012) had similar findings in a study that added a cap of organic residuals over mine tailings containing nickel and copper and showed no evidence of metal movement over the course of the 2 yr study. Evaluating trace metal accumulation in the roots of willows should be further investigated in future studies.…”
Section: Discussionsupporting
confidence: 64%
“…Renault et al (2000) also found that seedling survival in conifers was reduced to as low as 55% when grown directly in dry MFT. For this reason, adding a capping material plays an important role in reclamation by improving plant growth (Hargreaves et al 2012;Luna Wolter and Naeth 2014;Huang et al 2015), increasing water storage (Zettl et al 2011), and improving soil conditions to support self-sustaining ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, planting energy crops which can adapt to adverse conditions is considered to be a good choice, as it could potentially mitigate the soil contamination and the gradual reduction of fossil fuels at the same time (Olivares et al, 2013). As seen in reports, several researchers have postulated this new strategy of cultivating energy plants, including rapeseed, wheat, corn, castor bean, vetiver grass and willow in metalcontaminated soils for bioenergy production (Hargreaves et al, 2012;Liu et al, 2012;Luu Thai et al, 2011;Van Danh et al, 2007;Witters et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These results certainly suggest that there are environmental risks to this particular tailings revegetation strategy, even though the site is presently a productive forest. An alternative approach that is currently being tested at this site is the use of oxygen consuming organic covers [13,14,20]. This approach, while potentially accelerating the rehabilitation of the tailings, also requires more assessment of its suitability to prevent acid mine drainage particularly if more economical thin covers are used [20].…”
Section: Evaluation Of Risks To Tailings Stabilitymentioning
confidence: 99%
“…Such sites are typically carbon (C) and nutrient depleted, have a massive soil structure, contain high concentrations of metal contaminants and can be acid-generating [8]. An example of such a site, which also has a long and rich history of revegetation trials, can be found on the Vale waste management facility within the city of Greater Sudbury, Ontario, Canada [9][10][11][12][13][14]. In the region surrounding the city of Greater Sudbury, smelting activities in the 20th century created large areas of metal-contaminated, phytotoxic land, which have in many cases been successfully revegetated [15,16], a process that continues to be implemented through a regreening program.…”
Section: Introductionmentioning
confidence: 99%